SIPPABIO VS SPITCEROW: STUDI LITERATUR DUA MODEL PEMETAAN KONFLIK - Retno Angraeni S; M. Nurwahyudin S; Arnawan Arief; Mustakim Mustakim (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2026)
Conflict Mapping is a critically important analytical instrument in the study of peace and conflict resolution. This paper aims to provide an overview of two conflict mapping models, namely SIPABIO DAN SPITCEROW. Drawing on a literature review of relevant scholarly articles, this paper elaborates on the concepts, characteristics, and comparison of the two conflict mapping models. The findings indicate that SIPPABIO possesses elements that excel in unraveling the initial picture of a conflict, with the model emphasizing the psychological and relational dimensions of conflict. Meanwhile, SPITCEROW contains elements that help reconstruct the dynamics and escalation of conflict. These two mapping models are complementary and can be used for a more comprehensive conflict analysis. Through this paper, the author recommends that the selection of a model should depend on the research objectives, the characteristics of the conflict, and other contextual factors surrounding the conflict under study.